290 BREAST MILK FEEDING IN LOW BIRTH WEIGHT INFANTS: INFLUENCES AND BARRIERS. (1st January 2006) - Duffee, L. E.; Phillips, V.; Logan, A.; Howard, G.; Klapow, J.; Dimmitt, R. A.
Abstract : Background: Clinical studies have demonstrated that feeding human breast milk to premature infants can prevent several of the associated comorbid conditions. Often, the initial high rate of pumping breast milk at birth can wane by 1 month postpartum. Additionally, there appear to be socioeconomic and racial disparities in initiating and continuing to pump breast milk. The goal of this study was to determine these barriers in order to develop specific interventions to increase the rate of prolonged breast milk feeding. Methods: An extensive survey instrument was designed to ask questions about breastfeeding. Mothers of UAB inborn infants with a birth weight less than 1, 500 g and alive at 30 days were interviewed with the survey. The questions included maternal and infant demographic information. In addition, specific questions were designed to determine the prenatal influences regarding feeding, including breastfeeding. There were also questions pertaining to the immediate postpartum period as well as the first month about breast milk pumping. Three distinct populations were defined: never pumped, pumped but discontinued by 30 days, and those still providing breast milk at 30 days. The demographic information and the answers to the survey were used as variables and analyzed using logistic regression with a 95% confidence interval. Results: From July 1, 2003 to June 30, 2004, 102 mothers were surveyed. The median maternal age was 24 years. The racial composition was 54% white, 43% black, and 3% other. Almost 60% of the mothers had Medicaid. There was no difference in breast pumping rates based on race or socioeconomic status. Regarding initiation, 15% never attempted pumping while 58% were still pumping at 30 days. There was a strong association with not pumping in the mothers who had never considered breastfeeding in the prenatal period (OR 4.4, 95% CI 1.9, 19.1). The strongest prenatal influence regarding breastfeeding was the obstetrician (OB). The strongest factor associated with pumping breast milk at 30 days was husband/father of child involvement (OR 14.1, 95% CI 1.1, 174 and OR 9.3, 95% CI 2.2, 36, respectively). Conclusions: Prenatal OB and paternal influences were the strongest determinants in successful prolonged breast milk pumping. Implications: While important to provide postnatal lactation support, it appears that prenatal counseling is an major potential area for interventions designed to increase breastfeeding in general and possibly providing breast milk to premature infants.